Keys to Successful Land Administration : Lessons Learned in 20 Years of ECA Land Projects - Torhonen, Mika-Petteri (World Bank, Washington, DC, 2016)
The World Bank has funded land reform, land administration, and land management projects in the Europe and Central Asia (ECA) region since the early 1990s. The region comprises the 15 countries of the former Soviet Union, the former socialist countries of Central and Eastern Europe, and Turkey. Both the privatization of land and property assets and their efficient management and mobilization in the credit markets have been at the center of the transitional reforms to date. During this period, the World Bank has funded 42 land projects in 24 ECA countries in support of the land and property sector. This publication presents lessons learned from the past 20 years of ECA land projects. The findings stem from: a review of 27 implementation completion reports (ICRs) presented in annex one; an earlier work on the outcomes of ECA land projects; a project impact questionnaire completed by 13 ECA countries presented in annex two; and an economic impact assessment of 13 ECA land registration projects presented in annex three. These lessons learned provide a repository of knowledge on successful land projects in the context of countries in transition.